The prevalence of sickness absence among primary school pupils - reason to be worried? - Esther Karen Pijl; Yvonne Theodora Maria Vanneste; Angelique Eveline de Rijk; Frans Joseph Maria Feron; Jolanda Mathijssen (BMC, 2021)
Abstract Background Absence from school can lead to lower educational achievement and poor health. Little is known about school absence in primary education. This study's first aim was to examine the prevalence of school absence in primary schools and differing types of absence, including sickness absence. The second aim was to determine which pupil characteristics and types of absence were associated with extensive sickness absence. Methods The school absence registries for the school year 2015-2016 were analysed retrospectively in eight mainstream primary schools with 2216 pupils, and six schools for special primary education with 1000 pupils in the West-Brabant region of the Netherlands. Descriptive analyses, χ2-tests, Mann-Whitney U tests and logistic regression analyses were performed. Results The one-year prevalence of school absence was 85% in mainstream primary schools and 79% in special schools. Sickness absence was the most prevalent type of absence, occurring in 75 and 71% of pupils, respectively The prevalence of extensive sickness absence was 13 and 23%, respectively. In mainstream schools, extensive sickness absence was associated with a young age, low parental educational level, more doctor's visits and unauthorised absence, and in special schools with more doctor's visits, other authorised absence, tardiness and unauthorised absence. Conclusions The prevalence of extensive sickness absence was high, and as this was associated with other types of absence, these pupils missed even more days of school. Public health research, policy and practice should address sickness absence among primary school pupils, to prevent adverse effects on children's development.